Salespeople’s Work-Orientation Preference: An Exploratory Attributional Analysis of Intrinsic/Extrinsic Motivation - Sun, Jie (Journal of Applied Business and Economics, 2024)
Salespeople have different work attitude toward teamwork. Some of them value communication and coordination between team members, whereas others enjoy working on their own. It is believed that the discrepancies in work attitude derives from the different attribution styles, that is, whether people attribute failure outcomes to the external environment (e.g., lack of organizational support, unstable task situation, etc.) or to internal factors (e.g., self-ability, personal skills, consciousness, etc.). In addition, intrinsic/extrinsic motivation also comes into play during the formation of work-orientation preference. Using an attributional perspective, this article examines how different attribution styles influence the development of varying work attitude (team-orientation vs. self-orientation). Self-determination theory is also employed to explain the moderation role of intrinsic/extrinsic motivations.